A study of the relationship between internal marketing and customer satisfaction: a case study of Lobels bread Bulawayo - Nyauta, Sharon (Midlands State University, 2018)
Organizations are continuously seeking ways to improve their marketing effectiveness and orientation using internal marketing. Employees are the most important factor in the success and failure of any organization for the company to be at competitive advantage and dominate the market. The study therefore sought to study and evaluate the relationship between internal marketing and customer satisfaction. The objectives of the study were to establish the relationship between employee motivation and customer satisfaction, the relationship between meeting employee needs and customer satisfaction and also the relationship between employee empowerment and customer satisfaction. Literature was reviewed on research done on motivation, employee needs, employee empowerment and customer satisfaction. The methodology used was both quantitative and qualitative approach. A population sample of 65 participants was sampled from a total population of 193 members which included the employees of Lobels retail stores, their management and the customers involved was used to elicit the required data. Questionnaires and in- depth interviews were employed to collect data which was then analyzed using tables, bar charts, pie charts and discussions for better analysis and understanding. The findings show that employees were not motivated despite then management efforts to motivate them, the use of regression analysis showed that there is a positive relationship between employee motivation and customer satisfaction. Employees need to be involved more and empowered by the organization as there is also a strong positive relationship between employee empowerment and customer satisfaction. Meeting of employee needs is still also not to the level required by the employees. For customers to be satisfied the research findings show that there is a need for internal marketing and its strategies to be fully implemented. Conclusions made can sum up that there is a positive relationship between internal marketing and customer satisfaction which can be achieved with the use of the various factors mentioned above. Recommendations made include the need for the organization to rely on human resources. Management should also conduct efficient recruitment and selection. Training programs must be done often linking to the organizations objectives. Different methods of rewarding and compensating of employees should be practiced as a way to motivate them, and this should be done fairly basing on the market demands or needs.